Hubungan Disiplin Kerja dengan Kualitas Pelayanan Perawat Rawat Inap di RSU Sinar Husni - Hana Dhini julia Pohan; Sri Agustina Meliala; Dilla Fitria (Pelantar Press, 2026)
Nurses’ discipline remains relatively low, as evidenced by frequent tardiness, incomplete use of uniforms, and lack of courteousness toward patients. This study aimed to determine the relationship between work discipline and the quality of inpatient nursing services at Sinar Husni Hospital. This research employed a quantitative method with a cross-sectional design. The study population included all 93 inpatient nurses at the Hospital, with total sampling used as the sampling technique. Data were collected using a validated and reliable questionnaire, and analyzed using the chi-square test. The results found a significant relationship (p 0.05) between work discipline and service quality. Compliance with regulations on working hours, attendance, and rest breaks showed a significance value of p = 0.009; adherence to dress codes and professional behavior p = 0.016; compliance with procedures for task performance and work relations p = 0.003; and adherence to organizational rules on permissible and prohibited conduct p = 0.002. It is suggested that the hospital strengthen discipline through continuous guidance, consistent supervision, and the implementation of a fair reward-and-punishment system. Such efforts are expected to enhance nurses’ motivation, responsibility, professionalism, and performance in delivering excellent care.